2017
DOI: 10.1016/j.jcot.2016.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Management of post-traumatic neglected cervical facet dislocation

Abstract: Proper decompression, reduction and fixation should be done in neglected cervical dislocation as it provides mechanical stability and alignment, facilitates rehabilitation, prevent kyphotic deformity as well as offers a fair chance of neurological recovery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(27 citation statements)
references
References 15 publications
2
25
0
Order By: Relevance
“…This corresponds to other studies such as by Saha et al 17 in which they found the distribution of disease to be 58.33% in the dorsal region, which is the highest followed by 25% in the lumbar region and 16.67% in the thoracolumbar region. Regarding the maximum level of affection of the disease, our study also corresponds to the studies by Prabhat et al 18 in which the distribution of disease is maximum, that is, at the T5–T9 level. This has implied that the thoracolumbar spinal TB cases are more present at the dorsal region than the lumbar and junctional regions.…”
Section: Discussionsupporting
confidence: 85%
“…This corresponds to other studies such as by Saha et al 17 in which they found the distribution of disease to be 58.33% in the dorsal region, which is the highest followed by 25% in the lumbar region and 16.67% in the thoracolumbar region. Regarding the maximum level of affection of the disease, our study also corresponds to the studies by Prabhat et al 18 in which the distribution of disease is maximum, that is, at the T5–T9 level. This has implied that the thoracolumbar spinal TB cases are more present at the dorsal region than the lumbar and junctional regions.…”
Section: Discussionsupporting
confidence: 85%
“…Early management of these is critical for successful treatment and favorable outcome. [3] Delayed presentation is uncommon and especially seen in economically challenged countries. Guidelines for the management of neglected/delayed cases are unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Such patients can become chronic if they fail to seek medical attention or rarely a missed diagnosis. [ 2 ] The management of these neglected cases is a matter of debate and surgically a mammoth challenge keeping in mind the risks involved. [ 2 3 ] However, maintaining cervical stability and alignment is a major requisite in preventing progressive deformity and late-onset neurological deficit.…”
Section: Introductionmentioning
confidence: 99%
“…[ 2 ] The management of these neglected cases is a matter of debate and surgically a mammoth challenge keeping in mind the risks involved. [ 2 3 ] However, maintaining cervical stability and alignment is a major requisite in preventing progressive deformity and late-onset neurological deficit. [ 4 ] Surgeons have different algorithms for their patients, and here, we describe our technique in such a unique situation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation